Can a small New Keynesian model of the world economy with risk-pooling match the facts? - Patrick Minford; Zhirong Ou; Zheyi Zhu (Cardiff University, Cardiff Business School, 2019)
We ask whether a model of the US and Europe trading with the rest of the world can match the facts of world behaviour in a powerful indirect inference test. One version has uncovered interest parity (UIP), the other risk-pooling. Both pass the test but the most probable is risk-pooling. This is consistent with risk-pooling failing a number of single equation tests, as has been found in past work; we show that these tests will typically reject risk-pooling when it in fact prevails. World economic behaviour under risk-pooling shows much stronger spillovers than under UIP with opposite monetary responses to the exchange rate. We argue that the risk-pooling model therefore demands more attention from policy-makers.
Keywords: C12; E12; F41; 330; Open economy; UIP; risk-pooling; test; Indirect Inference